Analisis Penerapan Etika Bisnis Islam Dalam Persaingan Usaha Fashion Muslim Di Desa Pulau Mentaro Kabupaten Muaro Jambi - Ita Riani; Efni Anita; Awal Habibah (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
Competition in business is something that is often found in society, business competition between Muslim entrepreneurs in Mentaro Island villages on average sells the same products, it's just that the sales methods are different, some entrepreneurs experience a decrease in income and some experience an increase. Islamic business ethics are part of Muslim entrepreneurs in carrying out their business activities. Therefore, this thesis aims: 1. To find out business product competition between fashion entrepreneurs in Mentaro Island village. 2. To find out the services of entrepreneurs in implementing good Islamic business ethics. The research method used is a qualitative method. Qualitative research is a research procedure that produces descriptive data in the form of written or spoken words from people from observed behavior. The data collection techniques used are observation, interviews and documentation.The research results show 1. Business product competition between Muslim fashion entrepreneurs includes product competition, strategy, service and Islamic competition. Honesty, openness and good behavior. 2. Entrepreneur services in implementing good Islamic business ethics include Amanah, tabligh and Shiddiq. It is hoped that the results of this research will be useful for increasing knowledge, insight and input for all fashion entrepreneurs so that they can understand the application of Islamic business ethics in business competition.